Differential responses to child communicative behavior of parents of toddlers with ASD. (January 2021) - De Froy, Adrienne M; Sims, Megan E; Sloan, Benjamin M; Gajardo, Sebastian A; Rollins, Pamela Rosenthal
Background and aims: The quality of parent verbal input—diverse vocabulary that is well-matched to the child's developmental level within interactions that are responsive to their interests—has been found to positively impact child language skills. For typically developing (TD) children, there is evidence that more advanced linguistic and social development differentially elicits higher quality parent input, suggesting a bidirectional relationship between parent and child. The purpose of this study was to evaluate if toddlers with ASD also differentially elicit parental verbal input by (1) analyzing the quality of parent input to the communicative behavior of their toddlers with ASD, (2) examining if parents respond differentially to more advanced toddler communicative behavior, as measured by the coordination of multiple communicative behaviors, and (3) exploring the relationship between parental responsiveness to child communicative behaviors and change in child communication and social skills. Methods: Participants were 77 toddlers with ASD age 18-39 months and a parent who participated in a larger RCT. Ten-minute parent–toddler interactions were recorded prior to a 12-week intervention. Parent response to child communicative behaviors was coded following each child communicative behavior as no acknowledgment, responsive, directive, or nonverbal acknowledgment. Parent number of different words and difference between parent and child MLU in words were calculated separately for responsive and directive parent utterances. Child growth in language and social skills was measured using the Vineland II Communication and Socialization domain scores, respectively. Results: (1) Parents were largely responsive to their toddler's communication. When being responsive (as opposed to directive), parents used a greater number of different words within utterances that were well-matched to child language; (2) when toddlers coordinated communicative behaviors (versus producing an isolated communicative behavior), parents were more likely to respond and their replies were more likely to be responsive; and (3) parent responsiveness to child coordinated communication was significantly correlated with change in Vineland II Socialization but not Communication. A unique role of gaze coordinated child communication in eliciting responsive parental behaviors and improving growth in child social skills emerged. Conclusions: Our results support a bidirectional process between responsive parent verbal input and the social development of toddlers with ASD, with less sophisticated child communicative behaviors eliciting lower quality parent input. Implications : Our findings highlight the critical role of early parent-mediated intervention for children with ASD generally, and to enhance eye gaze through parent responsivity more specifically.